Biomarker-Calibrated Macronutrient Intake and Chronic Disease Risk among Postmenopausal Women. Issue 8 (20th April 2021) - Prentice, Ross L; Pettinger, Mary; Neuhouser, Marian L; Raftery, Daniel; Zheng, Cheng; Gowda, G A Nagana; Huang, Ying; Tinker, Lesley F; Howard, Barbara V; Manson, JoAnn E; Wallace, Robert; Mossavar-Rahmani, Yasmin; et al.
ABSTRACT: Background: Knowledge about macronutrient intake and chronic disease risk has been limited by the absence of objective macronutrient measures. Recently, we proposed novel biomarkers for protein, protein density, carbohydrate, and carbohydrate density, using established biomarkers and serum and urine metabolomics profiles in a human feeding study. Objectives: We aimed to use these biomarkers to develop calibration equations for macronutrient variables using dietary self-reports and personal characteristics and to study the association between biomarker-calibrated intake estimates and cardiovascular disease, cancer, and diabetes risk in Women's Health Initiative (WHI) cohorts. Methods: Prospective disease association analyses are based on WHI cohorts of postmenopausal US women aged 50–79 y when enrolled at 40 US clinical centers ( n  = 81, 954). We used biomarker intake values in a WHI nutritional biomarker study ( n  = 436) to develop calibration equations for each macronutrient variable, leading to calibrated macronutrient intake estimates throughout WHI cohorts. We then examined the association of these intakes with chronic disease incidence over a 20-y (median) follow-up period using HR regression methods. Results: In analyses that included doubly labeled water–calibrated total energy, HRs for cardiovascular diseases and cancers were mostly unrelated to calibrated protein density. However, many were inversely related to carbohydrate density, with HRs (95% CIs) for a 20% increment in carbohydrate density of 0.81 (0.69, 0.95) and 0.83 (0.74, 0.93), respectively, for primary outcomes of coronary heart disease and breast cancer, as well as 0.74 (0.60, 0.91) and 0.87 (0.81, 0.93) for secondary outcomes of heart failure and total invasive cancer. Corresponding HRs (95% CIs) for type 2 diabetes incidence in relation to protein density and carbohydrate density were 1.17 (1.09, 1.75) and 0.73 (0.66, 0.80), respectively. Conclusions: At specific energy intake, a diet high in carbohydrate density is associated with substantially reduced risk of major chronic diseases in a population of US postmenopausal women. This trial was registered at clinicaltrials.gov as NCT00000611.